IMPLEMENTASI ECONOMIC CIVIC DALAM MEMBENTUK KEMANDIRIAN SANTRI SEBAGAI GOOD GOVERNANCE - Muhamad Hijran; Rozi Rozi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Education is a vehicle for improving the quality of competitive human resources in nation building. The santri independence activity as a from of good governance is abig capital with development potential in increasing the people’s economic capaacity.The purpose of this study was to find out how the process of the people’s economic system at the Hidayatussalikin Modern Islamic Boarding School. The results showed the independence of students through civic knowledge, civic skill, and civic disposition made a positive contribution to students having soft skill and hard skill who were proficient and responsive in the implementation of Economic Civic si that they could meet their concumption needs and train their entrepreneurial spirit.